Investment Commitments to Energy Doubled in 2007 - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
This note states that in 2007 investment commitments to energy projects with private participation almost doubled in real terms compared with the activity in 2006, according to just-released data from the Private Participation in Infrastructure Project Database. The number of new energy projects grew by 8 percent.